DAMPAK REVITALISASI PERKEBUNAN PADA KOMODITAS KELAPA SAWIT TERHADAP PEREKONOMIAN PROVINSI JAMBI - Rizki Gemala Busyra (Universitas Batanghari Jambi, 2014)
In 2006 minister of agriculture policy, the Jambi province activities focused on the development commodity (palm oil), through expansion, renovation and rehabilitation of tree crops. Palm oil is one of the estate commodities is quite important for the Jambi economy, particularly as a provider of employment, sources of income and foreign exchange. Jambi Province is one of the largest palm oil producer in Indonesia. The purpose of this study is to identify the factors that affect the area, production, productivity, commodity prices and export in the Jambi province, and to analyze the impact of expansion areal palm oil on the economy of Jambi province. This study uses secondary data is structured as pooled annual data on nine districts in Jambi province, starting 2000 until 2009. The result of this study shows the expansion of palm oil can improve the economy of Jambi.Keywords: Econometric Model, Palm Oil, Jambi Province